Silencing of rape: treatment of rape events and rape victims by media and fiction - Shahid Ahmad,; Shanthi Nadarajan,; Ahmed Shamsul Bahari, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Sexual abuse affects over 120 million children globally (UNICEF, 2018). There has been a total of 48, 338 cases of rape of minors in India, with an increase of 336% from 2,113 in 2001 to 7,112 in 2011 (Gohain, 2013). In the US, almost half of female victims (46.7%) had been raped by an acquaintance (Breiding, 2014), with assaults (55%) occurring at or near the victim’s house (Planty & Langton, 2013). Each time a rape victim dies, there is public outcry with both press and writers’ calling for action but this has not helped the cause. Largely because “rape is not just forcible intercourse; rape means to inhabit and destroy everything” (Sebold, Lucky, 2002). This research analyses headlines and quotations on sexual crimes from mainstream online news from 2018 to 2019 from India and Malaysia. Using Austin’s Speech act theory, the study compares the voices of rape victims and witnesses and argues for a reason and social responsibility. The findings revealed significant differences in discourse patterns, language use, and witness response. In providing a worm’s eye view, Indian press in appearing to speak louder for victims, create greater sensationalism compared to Malaysian press which often focuses on the culprit and process of law and quickly silences the matter. Given media sensationalism and agenda setting of both nations, there is the need for greater scrutiny on how media provides a voice to victims and helps raise awareness and social responsibility when reporting sexual crimes.